Differences between the Spelling of an American and British English - Zoirovna, Murodova Sevara; Rahimova, Nazira (Journal of Innovation in Education and Social Research, 2024)
In this article it has been given information about the difference between American and English spelling rules and there were examples with the common distinctions, such as omitting the consonants and vowels in the lexis.